Penerapan Algoritma Rabin-Karp Pada Pencarian Sinonim Kata - Mega Oktaviani Pohan; Mesran; Ronda Deli Sianturi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Synonym is a word that has a different form but has the same or similar meaning or understanding. Synonyms are also known as word equations or word equivalents. Synonyms are used to express the sameness of meaning. In daily communication activities, language users still often make mistakes in using synonymous words. Often different linguistic forms are simply considered synonyms. Therefore, the correct mastery of synonyms must be possessed by language users for daily communication activities (both oral and written). The problem that has been faced so far is the lack of flexible means to facilitate the search for synonyms for these words. To overcome this problem, we need a simple application that is operated on an Android-based smartphone that is useful for helping us find synonyms for words. Users only need to enter the word they want to find synonyms for. This application will use a string matching algorithm or also known as String matching or is a method used to find an accuracy or result from one or several text patterns given. The expected results in this application are to help speed up the process of finding synonyms for Indonesian words, increase knowledge and vocabulary mastery of Indonesian users, especially synonyms